Addressing transgender patients' barriers to access care. Issue 6 (June 2019) - Rowe, Denise; Ng, Yeow Chye; O'Keefe, Louise C.
Abstract : Abstract: The transgender population faces several barriers to accessing quality medical care in the US healthcare system. This article examines the challenges that prevent this marginalized group from obtaining high-quality healthcare services and discusses how NP advocacy can help create a welcoming environment for transgender patients. Abstract : The transgender population faces several barriers to accessing quality medical care in the US healthcare system. This article examines the challenges that prevent this marginalized group from obtaining high-quality healthcare services and discusses how NP advocacy can help create a welcoming environment for transgender patients.